Quadruple, sequential, and concomitant first-line therapies for H. pylori eradication: a prospective, randomized study. Issue 2 (February 2018) - De Francesco, Vincenzo; Pontone, Stefano; Bellesia, Annamaria; Serviddio, Gaetano; Panetta, Cristina; Palma, Rossella; Zullo, Angelo
Abstract: Background: Current Italian guidelines recommend 10-day bismuth-based or bismuth-free (sequential and concomitant) regimens for first-line H. pylori eradication. However, comparison among these regimens is lacking in our country. Aim: To perform a 'head-to-head' comparison among these three therapies as first-line treatment for H. pylori eradication in clinical practice. Methods: This was a prospective, open-label randomized study enrolling consecutive patients diagnosed with H. pylori infection never previously treated. Patients were randomized to receive one of the following 10-day therapies: (a) Bismuth-based therapy: esomeprazole 20 mg b.i.d and Pylera 3 tablets q.i.d; (b) Concomitant therapy: esomeprazole 20 mg plus amoxicyllin 1, 000 mg, clarithromycin 500 mg and tinidazole 500 mg (all b.i.d.), and (c) Sequential therapy: esomeprazole 20 mg plus amoxicyllin 1, 000 mg for 5 days followed by esomeprazole 20 mg plus clarithromycin 500 mg and tinidazole 500 mg for 5 days (all b.i.d). H. pylori eradication was assessed by using UBT 4-6 weeks after the end of therapy. Results: Overall, 187 patients were enrolled. The eradication rates achieved with Pylera, concomitant and sequential were 85.2%, 95.2%, and 93.6%, respectively, at intention to treat, and 94.5%, 96.7%, and 95.1% at per protocol analyses, without a statistically significant difference. The incidence of severe side-effects was higher with the bismuth-based therapy than with the two bismuth-free regimens (9.8% vs 1.6%; p = 0.046). Conclusions: Bismuth-based and bismuth-free therapies are equally effective for first-line H. pylori eradication. However, bismuth therapy was more frequently interrupted for side-effects than bismuth-free therapies.